Pembelajaran Filologi Sebagai Salah Satu Upaya dalam Mengungkap dan Membangun Karakter Suatu Bangsa - Trie Utari Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The aim of the research to know, the importance of the role of philology in building the character of the nation that is by digging the moral values and character of the nation through research or cultivation of manuscript, both those that have been studied and that have not been analyzed by the philologists.The method used in this research is descriptive analytic method with qualitative approach. The results obtained from this study is the benefits of philology learning among which is to understand the culture of a nation, the unfolding of habits and customs of the people of the past, and the disclosure of the history of a real nation. With the unfolding of culture, customs, and history in the past, it will reveal the identity and character of a nation. One of them is through the cultivation of the text Anis Al-Muttaqin and Siksakandang Karesian script, in which contained moral values and character that should be owned by a leader.Conclusions In understanding the value of human behavior related to God, self, fellow human beings and the environment there is a need for philological learning in the form of texts. So that the value contained in the text appears to restore the nation's character. Keywords: Character, Philology Study